A Nonstandard Neutrosophic Model for Aesthetic Response in Interactive Device Decorative Art Design - Xing Wei (Neutrosophic Sets and Systems)
This paper introduces a new mathematical model called the Nonstandard Neutrosophic Aesthetic Dynamics (NSNAD). It is built using nonstandard neutrosophic theory, which allows us to work with values that are greater than 1, less than 0, or undefined. These unusual values help us better describe how users feel about decorative and interactive digital devices feelings that are often uncertain, extreme, or mixed. The model defines a new way to measure how much a person likes, dislikes, or is unsure about visual elements like light, color, shape, or movement. We use many refined equations and detailed examples to explain how the model works. We also apply the model to interactive device decoration to show its usefulness. This work helps designers better understand user emotions and build more personalized and engaging digital experiences.